New N4-Donor Ligands as Supramolecular Guests for DNA and RNA: Synthesis, Structural Characterization, In Silico, Spectrophotometric and Antimicrobial Studies - Ernest Ewert; Izabela Pospieszna-Markiewicz; Martyna Szymańska; Adrianna Kurkiewicz; Agnieszka Belter; Maciej Kubicki; Violetta Patroniak; Marta A. Fik-Jaskółka; Giovanni N. Roviello (Molecules, 2023)
The present work reports the synthesis of new N4-donor compounds carrying p-xylyl spacers in their structure. Different Schiff base aliphatic N-donors were obtained synthetically and subsequently evaluated for their ability to interact with two models of nucleic acids: calf-thymus DNA (CT-DNA) and the RNA from yeast Saccharomyces cerevisiae (herein simply indicated as RNA). In more detail, by condensing p-xylylenediamine and a series of aldehydes, we obtained the following Schiff base ligands: 2-thiazolecarboxaldehyde (L1), pyridine-2-carboxaldehyde (L2), 5-methylisoxazole-3-carboxaldehyde (L3), 1-methyl-2-imidazolecarboxaldehyde (L4), and quinoline-2-carboxaldehyde (L5). The structural characterisation of the ligands L1-L5 (X-ray, 1H NMR, 13C NMR, elemental analysis) and of the coordination polymers {[CuL1]PF6}n (herein referred to as Polymer1) and {[AgL1]BF4}n, (herein referred to as Polymer2, X-ray, 1H NMR, ESI-MS) is herein described in detail. The single crystal X-ray structures of complexes Polymer1 and Polymer2 were also investigated, leading to the description of one-dimensional coordination polymers. The spectroscopic and in silico evaluation of the most promising compounds as DNA and RNA binders, as well as the study of the influence of the 1D supramolecular polymers Polymer1 and Polymer2 on the proliferation of Escherichia coli bacteria, were performed in view of their nucleic acid-modulating and antimicrobial applications. Spectroscopic measurements (UV–Vis) combined with molecular docking calculations suggest that the thiazolecarboxaldehyde derivative L1 is able to bind CT-DNA with a mechanism different from intercalation involving the thiazole ring in the molecular recognition and shows a binding affinity with DNA higher than RNA. Finally, Polymer2 was shown to slow down the proliferation of bacteria much more effectively than the free Ag(I) salt.